Rebranding of NewsHunt to Dailyhunt: Dilemma of Future Direction. Issue 1 (December 2019) - Rishi, Bikramjit; Kacker, Archit; Hazra, Syamantak
Abstract: Dailyhunt's road to the number one regional language news aggregator in India had been a long and momentous one. Virendra Gupta, CEO and founder of Dailyhunt had seen the landscape undergo multiple changes and had to adapt his company to these changes through the use of analytics and strategic partnerships with content publishers. With the rapid penetration of internet usage in India, the new users of the internet were largely expected to be individuals who would be more comfortable consuming digital content in their native language. The potential this segment held was immense and Dailyhunt was in the driver's seat in terms of providing a personalized content stream and the large existing user base on its platform. However, with foreign investment pouring in for various new start-ups and the entry of several companies in to the segment, the challenges were set to increase, and Virendra Gupta had to decide what future strategies could help his company stand strong amidst the competition.